On the diet of Nile tilapia in two eutrophic tropical lakes containing toxin producing cyanobacteria - Semyalo, Ronald; Rohrlack, Thomas; Kayiira, Duncan; Kizito, Yusuf S.; Byarujali, Stephen; Nyakairu, George; Larsson, Petter (Limnologica, 2011)
Due to the production of toxins, cyanobacteria may adversely affect economically important fish such as Nile tilapia Oreochromis niloticus in tropical lakes. We studied the diet composition and factors affecting the diet of Nile tilapia in two tropical lakes where cyanotoxins were present. Particle-bound microcystins were present in all analysed water samples, ranging in concentration from 0.00012 to 1.11 and from 0.006 to 0.254 mg L1 in Murchison Bay in Lake Victoria and Lake Mburo, respectively. Detritus and phytoplankton were the main dietary components of the Nile tilapia, with phytoplankton contributing to over 30% by volume of stomach contents. The cyanobacteria Microcystis spp., which are also the most likely source of microcystins in the lakes, accounted for more than 80% of ingested phytoplankton. Microcystis spp. were also the most abundant cyanobacteria in both lakes (460%). We found no significant relationship between the contribution of phytoplankton in Nile tilapia diet and the concentration of microcystins in the water but we found a close association between water transparency and the contribution of insects to Nile tilapia diets in Murchison Bay. Our results further show that none of the other measured environmental variables was a good predictor of diet items in Nile tilapia. Adult Nile tilapia in our study lakes, rely heavily on filter feeding, particularly under conditions of low water transparency, trapping detritus and phytoplankton cells especially colonies. They can ingest more mobile prey like insects and insect larvae when the water transparency and visibility increases.
Keywords: Nile tilapia; Diet; Microcystins; Cyanobacteria; Tropics